Inverse association of resistin with physical activity in the general population. - Itahisa Marcelino-Rodríguez; Delia Almeida Gonzalez; José Juan Alemán-Sánchez; Buenaventura Brito Díaz; María Del Cristo Rodríguez Pérez; Fadoua Gannar; Santiago Domínguez Coello; Francisco J Cuevas Fernández; Antonio Cabrera de León (PLoS ONE)
Aim Resistin is a cytokine related with inflammation and ischemic heart disease. Physical activity (PA) prevents chronic inflammation and ischemic heart disease. We studied the relationship of serum concentration of resistin with HDL cholesterol, a known biomarker of PA, and with different measures of PA, in a large sample of the general adult population in the Canary Islands. Methods Cross-sectional study of 6636 adults recruited randomly. We analyzed the correlation of resistin and HDL cholesterol with PA (as metabolic equivalent level [MET]), and fitted the results with linear and logistic regression models using adjustment for age, alcohol consumption and smoking. Results Mean resistin level was higher in women (p<0.001), correlated inversely with age, HDL cholesterol (p<0.001) and alcohol consumption (p<0.001 in men), and correlated directly with smoking (p<0.001). Resistin correlated inversely with the duration of leisure time PA (p<0.001), leisure time MET (p<0.001) and moderate leisure time PA (p<0.001), with some differences between sexes. Men (OR = 0.78 [0.61-0.99; p<0.05]) and women (OR = 0.75 [0.61-0.92; p<0.01]) in the upper quintile of leisure time PA had a lower risk of elevated resistin. In contrast, a high degree of sedentarism was associated with an increased risk elevated resistin in women (OR = 1.24 [1.04-1.47; p<0.05] and in men (OR = 1.40 [1.01-1.82; p<0.05]). Conclusions In our sample of the general population, resistin was inversely associated with measures and levels of PA and HDL cholesterol. The association of resistin with PA was stronger than the association of HDL cholesterol with PA, making resistin a potentially useful biomarker of PA.